Effects of weaning on body condition recovery and calf performance in previously nutritionally restricted cow-calf pairs - Ward, M.A.; Johnson, Sandra K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2013)
Drought, defined as less than 75% of normal rainfall, occurs once every 5 to 7 years in Northwest Kansas. Record widespread drought conditions throughout the Midwest and Western United States in 2012 resulted in an early reduction in forage quality and availability. In these situations, cow-calf producers are faced with deciding how to adapt to the conditions. Some producers may be unprepared for the speed at which cows can lose body condition in the face of declining pasture conditions and how much it takes to regain body condition. Early weaning is one option that can improve a cow’s nutritional status, conserve forage, and delay the need for supplementation. The price slide between lightweight early weaned calves and heavier calves is an important factor in the economic outcome of that decision. Feed use and cow and calf performance data are needed to evaluate production and economic differences between early and normal weaning scenarios. The objective of this study was to quantify intake differences between dry and lactating cows that had previously been nutritionally restricted and measure feed consumed by calves still nursing dams.
Keywords: Swine; Weaning; Performance data; Nutrition